Science opportunities enabled by NASA's constellation system interim report (National Academies Press, 2008)
To begin implementation of the Vision for Space Exploration (recently renamed United States Space Exploration Policy), NASA has begun development of new launch vehicles and a human-carrying spacecraft that are collectively called the Constellation System. In November 2007, NASA asked the NRC to evaluate the potential for the Constellation System to enable new space science opportunities. For this interim report, 11 existing Vision Mission studies of advanced space science mission concepts inspired by earlier NASA forward-looking studies were evaluated. The focus was to assess the concepts and group them into two categories: more-deserving or less deserving of future study.